Local and import material procurement risk analysis: house of risk method: (Case Study at Bio-Manufacturing Company) - Kurniawan, Syahriza; Wiyarni, Wiyarni (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Global challenges require companies to be able to manage their supply chain processes well. The procurement process is an important part of the supply chain because it can reduce total costs. Procurement strategies not only focus on reducing material prices but also controlling supply risks. To maintain competitiveness and create a stable supply of materials, PT. X sources materials locally or imports from abroad. This condition causes the potential for high risks to arise in the procurement process. At PT. X, risk analysis has not been conducted for either local or imported material procurement. Research is needed to map risks and mitigate them. A popular method used for risk identification and mitigation is the House of Risk (HOR). Many studies have been conducted on the HOR method, but no comparison has been made between its application in local and imported material procurement. Research is needed to map risks and mitigate them. A popular method used for risk identification and mitigation is the House of Risk (HOR). Many studies have been conducted on the HOR method, but no comparison has been made on the application of HOR to the procurement of local and imported materials. The procurement process is identified based on its sub-processes using the SCOR (Supply Chain Operation Reference) method. HOR phase 1 produces 25 risk events and risk agents for both local and imported materials. In HOR phase 2, the Aggregate Risk Potential (ARP) is calculated and ranked from the highest to the lowest value. Imported materials tend to have a high ARP value, meaning they have a higher risk than local materials. Using the Pareto principle, 5 priority risk agents are obtained that need to be mitigated. HOR phase 2 produces 10 preventive actions (PA) that can be used to mitigate risks. In HOR phase 2, calculations are carried out to obtain the Effectiveness to Difficulty (ETD) ratio and are ranked from the highest to the lowest value. Imported materials tend to have a high ETD value, meaning they have a high priority. From the risks of local materials and imported materials, risk mitigation using preventive actions is prioritized on risk agents with the highest to the lowest ETD values.